IMPLEMENTASI JARINGAN NIRKABEL XBEE PRO S2C DAN ESP8266 UNTUK PEMANTAUAN LOKASI PARKIR - Morlan Pardede; Elferida Hutajulu; Regina Sirait (Jurnal Mantik Penusa)
Due to the lack of information on the location of empty parking slots and the difficulty of users seeing empty parking slots in large parking locations, users need a relatively long time to find an empty parking slot. This study describes how to inform the location of empty parking slots and the number of parking slots available in a parking zone to parking managers and users with the XBee Pro S2C wireless networks. In this system the parking location is divided into 3 (three) zones and each parking zone is equipped with a sensor node consisting of Arduino Mega 2560, ultrasonic sensor HC-SR04, XBee ProS2C and ESP8266 . Sensor nodes for each zone detect empty parking slots, calculate the number of vehicles and send parking zone information to the monitoring center via a wireless network so that parking attendants can see parking information from each zone on the monitoring center computer. Parking information is also sent by the sink node to the webserver using ESP8266 and the ThingSpeak.com webserver so users can access parking information via the internet. By implementing Zigbee XBee Pro S2C network firmware can expand parking spot monitoring.